A low-noise photonic heterodyne synthesizer and its application to millimeter-wave radar - Eric A. Kittlaus (Nature Portfolio, 2021)
Photonics-based radars offer intriguing potential but face tradeoffs in tunability, complexity, and noise. Here the authors present microwave generation in a photonics platform by heterodyning of two low-noise, self-injection-locked lasers, and demonstrate its advantages in an FMCW radar system.